Quantittative Analysis of Amount and Activity of Ficin in Khorasan's Fig Tree Latex Retrieved from Different Organs of Tree in Different Seasons - O Rajabi; J Danaie Baghaki; AR Varasateh; L Jahangiri; A Baratian (Institue of Medicinal Plants, ACECR, 2006)
Background: The fig tree latex has been identified as a rich resource of "ficin" an enzyme protein. This enzyme has a vast application in food substances, pharmaceutical and clinical diagnosis, Fig plant can be harvested well in Khorasan province. Objective: To determine optimum organ and season to retrieve latex for different purposes. Method: In this study the measuring of the enzyme activity was based on its effect of casein substrate. Enzymatic activity was compared with standard papain solution activity. In this research calcium ion concentration as an enzyme activator was studied. Findings: The results show that the activity of the Khorasan native fig latex was 50-100 fold more than papain. The amount and the activity of ficin have been variant in different organs of the tree, and also varied with season. Calcium ion concentrations are also variable in different organs and are also season dependent. There is a relationship between calcium ion concentrations and specific activity of ficin. Results: The optimum season for latex collection is fall and the best organ is the branch ends.